4-(Furan-2-ylmethoxy)benzene-1,2-dicarbonitrile - Tuncer, Hulya; Gorgulu, Ahmet Orhan; Hokelek, Tuncer (Int Union Crystallography, 2012)
In the title compound, C13H8N2O2, prepared from furfuryl alcohol and 4-nitrophthalonitrile in the presence of potassium carbonate in dimethylformamide, the furan and benzene rings are oriented at a dihedral angle of 53.45 (9)degrees. In the crystal, weak C-H center dot center dot center dot O and C-H center dot center dot center dot N hydrogen bonds link the molecules into a three-dimensional network.